2015
DOI: 10.1039/c4ra12556h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two-color laser pulse intensity ratio on intense terahertz generation

Abstract: We theoretically demonstrate the effect of intensity ratio of the two-color laser field on the terahertz generation based on a transient photocurrent model. We show that the terahertz generation depends on the intensity ratio of the two-color laser field at a given total laser intensity, and the optimal intensity ratio for the maximum terahertz generation will decrease with the increase of the total laser intensity. We also show that the final ionization degree can be used to explain the optimal intensity rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In our simulation, the amplitude of the fundamental laser pulse E 0 is so set so that a moderate ionization degree W fi = 0.4 is produced at the standard five-color pulse, since the effects of the laser parameters will be different at higher laser intensities. [33,34] Once freed from the parent molecule, the electron will oscillate with the laser field, and the electron velocity at a subsequent time can be written as…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In our simulation, the amplitude of the fundamental laser pulse E 0 is so set so that a moderate ionization degree W fi = 0.4 is produced at the standard five-color pulse, since the effects of the laser parameters will be different at higher laser intensities. [33,34] Once freed from the parent molecule, the electron will oscillate with the laser field, and the electron velocity at a subsequent time can be written as…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In the scheme of interaction of intense laser field with gases, the commonly used driving field is a combination of a fundamental linearly polarized pulse and its second harmonic [14,15], for the linearly polarized THz generation. In order to enhance the THz radiation intensity, the duration of the pump pulse [16,17], phase delay [14,15,18,19] and intensity ratio between two pulses [20,21], should be carefully optimized. With these efforts, the THz pulse energy can be increased by at least one order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…However, yield of emitted terahertz radiation depends on helicity of the laser pulses and it is maximum when the helicity is same [30]. Experimental studies based on two-colour laser pulses propagating in plasma have shown that higher the intensity ratio of the two laser pulses, lower will be the intensity of emitted terahertz radiation [31]. Also, the intensity of generated terahertz radiation depends on phase of the two-colour laser pulses.…”
mentioning
confidence: 99%